2022
DOI: 10.1039/d2cp02540j
|View full text |Cite
|
Sign up to set email alerts
|

The hitchhiker's guide to dynamic ion–solvent clustering: applications in differential ion mobility spectrometry

Abstract: This article highlights the fundamentals of ion-solvent clustering processes that are pertinent to an ion’s behaviour during differential mobility spectrometry (DMS) experiments. We contrast static-field ion mobility with differential ion...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 14 publications
(42 citation statements)
references
References 169 publications
1
41
0
Order By: Relevance
“…The separation power afforded by DMS can be enhanced by doping the DMS carrier gas with solvent vapor. The increase in separation power is a consequence of microsolvation, which increases the difference between the ion’s high and low-field mobility and is usually ion-specific. This phenomenon is rooted in the heating/cooling cycles associated with the field-induced temperature imparted by the SV, where the oscillating waveform drives analyte solvation/desolvation cycles as the ion transitions between the low-field to the high-field portion of the duty cycle. Mashmoushi et al showed that optimal sensitivity and resolution was afforded by detecting the cannabinoids as deprotonated anions in a N 2 DMS environment that is seeded with 1.5 mol % of IPA . However, our attempts to add Δ 8 -THC to this workflow resulted in its coelution with CBD using various chemical modifiers (Figures S2 and S3), indicating that an alternative separation strategy will be required.…”
Section: Introductionmentioning
confidence: 98%
“…The separation power afforded by DMS can be enhanced by doping the DMS carrier gas with solvent vapor. The increase in separation power is a consequence of microsolvation, which increases the difference between the ion’s high and low-field mobility and is usually ion-specific. This phenomenon is rooted in the heating/cooling cycles associated with the field-induced temperature imparted by the SV, where the oscillating waveform drives analyte solvation/desolvation cycles as the ion transitions between the low-field to the high-field portion of the duty cycle. Mashmoushi et al showed that optimal sensitivity and resolution was afforded by detecting the cannabinoids as deprotonated anions in a N 2 DMS environment that is seeded with 1.5 mol % of IPA . However, our attempts to add Δ 8 -THC to this workflow resulted in its coelution with CBD using various chemical modifiers (Figures S2 and S3), indicating that an alternative separation strategy will be required.…”
Section: Introductionmentioning
confidence: 98%
“…Because the exact magnitude of the DR-induced temperature gradient is not known, it was necessary to explore whether invariant CV behavior would also be observed using a more controlled method to change the effective temperature ( T eff ) of the ion . The T eff of an ion is determined by the sum of the temperatures of the bath gas ( T bath ) and the electric field ( T field ) as described by two-temperature theory. , Since a relatively high SV is needed to resolve the [Hum + Ag] + tautomers, T eff can only be modulated by changing T bath , which is determined by the DT setting.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Recently, we have reported correlations between gas-phase dynamic ion-solvent clustering behavior and solution-phase p-chem properties. We hypothesize that the clustering process effectively samples the ion-solvent interaction potential and that the gas-phase interactions correlate strongly with the condensed phase interactions that give rise to p-chem properties such as lipophilicity. To use these data to create general predictive models for p-chem properties of interest, it is necessary to treat dynamic clustering data with supervised machine learning (ML).…”
Section: Introductionmentioning
confidence: 99%